2017
DOI: 10.1104/pp.17.00366
|View full text |Cite
|
Sign up to set email alerts
|

Unique Motifs and Length of Hairpin in Oleosin Target the Cytosolic Side of Endoplasmic Reticulum and Budding Lipid Droplet

Abstract: Plant cytosolic lipid droplets (LDs) are covered with a layer of phospholipids and oleosin and were extensively studied before those in mammals and yeast. Oleosin has short amphipathic N-and C-terminal peptides flanking a conserved 72-residue hydrophobic hairpin, which penetrates and stabilizes the LD. Oleosin is synthesized on endoplasmic reticulum (ER) and extracts ER-budding LDs to cytosol. To delineate the mechanism of oleosin targeting ER-LD, we have expressed modifiedoleosin genes in Physcomitrella paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 62 publications
4
35
0
Order By: Relevance
“…LD proteins can target the LD surface either by binding the lipids of the phospholipid monolayer and/or neutral lipid core or by associating with other coat proteins (Kory et al ., ; Bersuker and Olzmann, ). In general, they are divided into two classes: class I proteins, including the oleosins, which target to the LD surface via the ER (Huang and Huang, ), and class II proteins, which target directly from the cytoplasm. When transiently over‐expressed in tobacco leaf cells, Cherry‐LDIP localized to LDs and the cytoplasm, but was never observed in association with the ER, even after extended periods of transient expression in tobacco (Figure S12) or when stably (ectopically) expressed in Arabidopsis plants (Figure S10), suggesting that LDIP is a class II‐type LD protein.…”
Section: Discussionmentioning
confidence: 99%
“…LD proteins can target the LD surface either by binding the lipids of the phospholipid monolayer and/or neutral lipid core or by associating with other coat proteins (Kory et al ., ; Bersuker and Olzmann, ). In general, they are divided into two classes: class I proteins, including the oleosins, which target to the LD surface via the ER (Huang and Huang, ), and class II proteins, which target directly from the cytoplasm. When transiently over‐expressed in tobacco leaf cells, Cherry‐LDIP localized to LDs and the cytoplasm, but was never observed in association with the ER, even after extended periods of transient expression in tobacco (Figure S12) or when stably (ectopically) expressed in Arabidopsis plants (Figure S10), suggesting that LDIP is a class II‐type LD protein.…”
Section: Discussionmentioning
confidence: 99%
“…Plant LBs can contain a variety of proteins, including OLEOSINS, CALEOSINS, STEROLEOSINS [2,5], LDAPs, and LDIP [36]. In seeds, the extraction of LBs from the ER is controlled solely by the LB-specific integral protein OLEOSIN [3,7,37]. OLEOSINs are small 15-26 kD proteins that are inserted co-translationally into the ER-membrane, with the termini located in the cytosol, and the central hydrophobic hairpin positioned under strain in the ER bilayer [37] similarly to GPAT4 [28].…”
Section: Introductionmentioning
confidence: 99%
“…In seeds, the extraction of LBs from the ER is controlled solely by the LB-specific integral protein OLEOSIN [3,7,37]. OLEOSINs are small 15-26 kD proteins that are inserted co-translationally into the ER-membrane, with the termini located in the cytosol, and the central hydrophobic hairpin positioned under strain in the ER bilayer [37] similarly to GPAT4 [28]. From this unstable position the OLEOSIN molecule will diffuse into an emerging oil lens, extracting it from the ER while relaxing its hydrophobic hairpin in the lipid core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For direct localization, specific domains have been identified that are integral monotopic structures including hydrophobic domains or/and amphipathic α-helixes (Bersuker and Olzmann, 2017;Kory et al, 2016). The targeting formats include hydrophobic hairpin, terminal hydrophobic domain, and nonterminal hydrophobic domains (Boeszoermenyi et al, 2015;Huang and Huang, 2017;Na et al, 2015). In addition, one or more amphipathic α-helixes could be also involved (Ding et al, 2012;Krahmer et al, 2011), a type of motif that is characteristic of LD resident proteins (Bulankina et al, 2009;Chong et al, 2011;Rowe et al, 2016;Subramanian et al, 2004).…”
Section: Introductionmentioning
confidence: 99%